An overview of using small punch testing for mechanical characterization of MCrAlY bond coats - Chen, Hao; Jackson, G.A.; Sun, Wei (Springer, 2017)
Considerable work has been carried out on overlay bond coats in the past several decades because of its excellent oxidation resistance and good adhesion between the top coat and superalloy substrate in the thermal barrier coating systems. Previous studies mainly focus on oxidation and diffusion behavior of these coatings. However, the mechanical behavior and the dominant fracture and deformation mechanisms of the overlay bond coats at different temperatures are still under investigation. Direct comparison between individual studies has not yet been achieved due to the fragmentary data on deposition processes, microstructure and, more apparently, the difficulty in accurately measuring the mechanical properties of thin coatings. One of the miniaturized specimen testing methods, small punch testing, appears to have the potential to provide such mechanical property measurements for thin coatings. The purpose of this paper is to give an overview of using small punch testing to evaluate material properties and to summarize the available mechanical properties that include the ductile-to-brittle transition and creep of MCrAlY bond coat alloys, in an attempt to understand the mechanical behavior of MCrAlY coatings over a broad temperature range.